2020
DOI: 10.1007/s10707-020-00407-w
|View full text |Cite|
|
Sign up to set email alerts
|

MongoDB Vs PostgreSQL: A comparative study on performance aspects

Abstract: Several modern day problems need to deal with large amounts of spatio-temporal data. As such, in order to meet the application requirements, more and more systems are adapting to the specificities of those data. The most prominent case is perhaps the data storage systems, that have developed a large number of functionalities to efficiently support spatio-temporal data operations. This work is motivated by the question of which of those data storage systems is better suited to address the needs of industrial ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 18 publications
0
18
0
3
Order By: Relevance
“…Resource for Geospatial Information and Standards (Makris et al, 2021). PostGIS adds a spatial aspect to the PostgreSQL server, and the server becomes eligible to be used as a backend spatial database for geographic information systems (GIS).…”
Section: The Database (Design and Creation)mentioning
confidence: 99%
See 1 more Smart Citation
“…Resource for Geospatial Information and Standards (Makris et al, 2021). PostGIS adds a spatial aspect to the PostgreSQL server, and the server becomes eligible to be used as a backend spatial database for geographic information systems (GIS).…”
Section: The Database (Design and Creation)mentioning
confidence: 99%
“…PostGIS adds a spatial aspect to the PostgreSQL server, and the server becomes eligible to be used as a backend spatial database for geographic information systems (GIS). It adds special geometry data types and spatial function to the PostgreSQL object-relational database (Makris et al, 2021).…”
Section: The Database (Design and Creation)mentioning
confidence: 99%
“…A dataset 4 with sparse points which contains the trajectory information of three animal species from Starkey project. In this dataset, major habitat variables derived for radiotelemetry studies of elk, mule deer and cattle at the Starkey Experimental Forest and Range, 28 miles southwest of La Grande, Oregon.…”
Section: Animals Datasetmentioning
confidence: 99%
“…For instance, one AIS 1 -receiving station receives 6 AIS messages, or 1800 bytes, per second. Considering that a ship tracking company may operate thousands of such receivers, we end up with terabytes of data to deal with each month [4]. For example, MarineTraffic's on-line monitoring service collects 60Mb of AIS and weather data every second [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [4], the comparison is made in terms of the response time in a 5 node cluster, which showed that PostgreSQL outperformed MongoDB in all cases. The speedup of PostgreSQL over MongoDB was on average above 2.6, clearly showing the superiority of PostgreSQL when it comes to query handling.…”
Section: Literature Reviewmentioning
confidence: 99%